INESTABILIDAD LABORAL EN EL SECTOR PÚBLICO, EN RELACIÓN A LOS DOS AÑOS DE CONTRATO - Galván Arias, Sara Elizabeth (2016)
Job instability spanning servers, servants and public workers today, seriously affecting people who serve in public institutions, as well as the family and the same state, you have to see to the procurement of services occasional that they are established in the Organic Law on Public Service (LOSEP). The job instability that currently live in our country, is unconstitutional, and that today has been violating enshrined in our Constitution of the Republic of Ecuador, with the enactment of new laws and regulations, as well as presidential decrees rights are lower hierarchy that our Constitution, that all they do is violate the rights of people who have been consecrated since our supreme law, and that therefore we guarantee all those rights that must be respected by the competent authorities and to comply with the boss our constitution. The state little or nothing interested him enforce constitutional guarantees that are established in our supreme law regarding the right to work, since it is a source of personal fulfillment, the state guarantee to working people a decent life, with fair wages and healthy work freely chosen or accepted, people currently serving are very insecure in their jobs by not having a steady job and organize their personal and family lives, since not having job security do not have the capabilities to acquire some good for their families and so be able to offer a better quality of life.